The Effect of Providing Feedback on Student Achievement - Rahmi Yati; Suharman Suharman; M. Rezki Andhika (ISTIFHAM, 2023)
Student learning outcomes can be used as a benchmark to assess whether a school's education is successful. While learning outcomes are influenced by various factors, one of which is the provision of feedback by an educator in the learning process. An educator does this to create a fun and interesting classroom environment so that students can hone their creativity in thinking, which will impact increasing student learning outcomes. The results of this study concluded that there was an effect of providing feedback on student learning outcomes. This is evident from hypothesis testing using the regression formula obtained results of 0.35. So in this study, the alternative hypothesis (Ha) is accepted, and (Ho) is rejected, with a low level of relationship. Then, look for the effect of providing feedback using the simple regression formula with the result y = 0.066 + 0.298x in influencing student learning outcomes. Furthermore, from the calculation of the coefficient of determination for the effect of giving feedback, it has a contribution or influence of 1.26%. Then the rest is influenced by other factors, such as internal and external factors. Based on the explanation above, it can be concluded that the effect of providing feedback on student learning outcomes is low.